Vzgliad . Vzgliad . Viewpoint . Взгляд - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. The program raises awareness about problems related to teenagers: drug addiction, crime, neo-Nazism. Series description: A TV program of the Central Television (CT) and the First Channel (ORT). Produced by the USSR State Committee for Television and Radio Broadcasting (1987-1990) and TV company VID (since October 1990). First aired in October 1987. Its main hosts were Oleg Vakulovskii, Dmitri Zakharov, Vladislav Listiev, and Aleksander Lyubimov. This was one of the most popular TV program on Russian TV in 1987-2001. In 1988-1991 the program’s scenarios were made by TV Company ATV, and from 1994 to 1995 the program was issued jointly with the studio “Publitsist” of the Russian State Television and Radio Broadcasting Company “Ostankino.” О проблемах подростков: наркомания, преступность, неонацизм. Описание серии: Телепрограмма Центрального телевидения и Первого канала (ОРТ). Производители — Главная редакция программ для молодёжи ЦТ Гостелерадио СССР (1987—1990) и Телекомпания ВИД (с 5 октября 1990 года). Официально выходила в эфир со 2 октября 1987 года. Ведущие первых выпусков программы: Олег Вакуловский, Дмитрий Захаров, Владислав Листьев и Александр Любимов. Это была наиболее популярная передача в 1987—2001 гг. В 1988—1991 годах сюжеты для программы делала телекомпания АТВ, а с 1994 по 1995 год программа выпускалась совместно со студией «Публицист» РГТРК "Останкино."